Risk factors associated with acute exacerbation of chronic obstructive pulmonary disease in HIV-infected and uninfected patients. (28th January 2016) - Depp, Timothy B.; McGinnis, Kathleen A.; Kraemer, Kevin; Akgün, Kathleen M.; Edelman, E. Jennifer; Fiellin, David A.; Butt, Adeel A.; Crystal, Stephen; Gordon, Adam J.; Freiberg, Matthew; Gibert, Cynthia L.; Rimland, David; et al.
Abstract : Objective: To determine the association between HIV infection and other risk factors for acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Design: Longitudinal, national Veterans Aging Cohort Study including 43 618 HIV-infected and 86 492 uninfected veterans. Methods: AECOPD was defined as an inpatient or outpatient COPD ICD-9 diagnosis accompanied by steroid and/or antibiotic prescription within 5 days. We calculated incidence rate ratios (IRR) and 95% confidence intervals (CI) for first AECOPD over 2 years and used Poisson regression models to adjust for risk factors. Results: Over 234 099 person-years of follow-up, 1428 HIV-infected and 2104 uninfected patients had at least one AECOPD. HIV-infected patients had an increased rate of AECOPD compared with uninfected (18.8 vs. 13.3 per 1000 person-years, P  < 0.001). In adjusted models, AECOPD risk was greater in HIV-infected individuals overall (IRR 1.54; 95% CI 1.44–1.65), particularly in those with more severe immune suppression when stratified by CD4 + cell count (cells/μl) compared with uninfected (HIV-infected CD4 +  < 200: IRR 2.30, 95% CI 2.10–2.53, HIV-infected CD4 + ≥ 200–349: IRR 1.32, 95% CI 1.15–1.51, HIV-infected CD4 +  ≥ 350: IRR 0.99, 95% CI 0.88–1.10). HIV infection also modified the association between current smoking and alcohol-related diagnoses with risk for AECOPD such that interaction terms for HIV and current smoking or HIV and alcohol-related diagnoses were each significantly associated with AECOPD. Conclusion: HIV infection, especially with lower CD4 + cell count, is an independent risk factor for AECOPD. Enhanced susceptibility to harm from current smoking or unhealthy alcohol use in HIV-infected patients may also contribute to the greater rate of AECOPD.